English Teachers’ Perspective Towards the Implementation of Curriculum 2013 - Pompana, Seprianto; Pilongo, Jolanda H. D.; Mestari, Sri Agriyanti (Research Review: Jurnal Ilmiah Multidisiplin, 2023)
This study aimed to know the perspective of English teachers towards the implementation of the 2013 curriculum at SMP Negeri 16 Gorontalo. The participants in this study were English teachers consisting of 2 teachers who taught classes V11 to 1X for the 2022/2023 academic year. This study uses a descriptive qualitative method with data collection techniques using interviews and documentation (Sugiyono, 2016). This study also uses the data analysis model of Miles and Huberman (1984), as cited in Sugiyono (2016). The interview indicators were adapted and developed from the fourteen learning principles of the 2013 curriculum in Permendikbud number 22 of 2016. The results of this study indicate that English teachers have quite well implemented the implementation of the 2013 curriculum. It is evident from the teacher's strategy in implementing the 2013 curriculum learning principles. However, several principles still have not met the 2013 curriculum learning expectations and the obstacles encountered by English teachers. Some of the teacher obstacles in implementing the 2013 curriculum include limited learning resources, teacher readiness, book sources that are difficult to understand, lack of training or workshops on implementing the 2013 curriculum, assessment formulation, lack of teacher understanding in integrated learning, lack of student participation and confidence, and limited facilities and infrastructure.